Optimization of the injection molding parameters using the Taguchi method / Shahrul Kamaruddin, Zahid A. Khan and K. S. Wan (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2006)
In this study, the Taguchi method, a powerful tool to design and process optimization for quality, is used to determine the optimal parameters for an injection molding process. An orthogonal array, the signal-to-noise (S/N) ratio and the analysis of variance (ANOVA) are employed to investigate the quality characteristics of aplastic tray which is made on an injection molding machine from polypropylene (PP) plastic material. Through this study, not only the optimal molding parameters for an injection molding process can be obtained, but also the main parameters that affect the performance of the tray can be obtained. Experimental results are provided to confirm the effectiveness of this approach.